2005
DOI: 10.1007/s00382-005-0090-8
|View full text |Cite
|
Sign up to set email alerts
|

Five hundred years of gridded high-resolution precipitation reconstructions over Europe and the connection to large-scale circulation

Abstract: We present seasonal precipitation reconstructions for European land areas (30°W to 40°E/30-71°N; given on a 0.5°•0.5°resolved grid) covering the period 1500-1900 together with gridded reanalysis from 1901 to 2000 (Mitchell and Jones 2005). Principal component regression techniques were applied to develop this dataset. A large variety of long instrumental precipitation series, precipitation indices based on documentary evidence and natural proxies (tree-ring chronologies, ice cores, corals and a speleothem) tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
623
1
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 441 publications
(664 citation statements)
references
References 87 publications
38
623
1
2
Order By: Relevance
“…Over the past few decades, there have been a number of severe and/or persistent drought and heat episodes in the countries bordering the Mediterranean, including Turkey (Luterbacher et al, 2004;Pauling et al, 2006). Such extreme events can have disastrous consequences for human society due to resulting famine and disease, soil degradation, desertification, and increased incidence of wildfires (di Castri and Mooney, 1973;Le Houérou, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few decades, there have been a number of severe and/or persistent drought and heat episodes in the countries bordering the Mediterranean, including Turkey (Luterbacher et al, 2004;Pauling et al, 2006). Such extreme events can have disastrous consequences for human society due to resulting famine and disease, soil degradation, desertification, and increased incidence of wildfires (di Castri and Mooney, 1973;Le Houérou, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…One purported advantage is the inclusion of longrange correlation structures, leading to predictive skill even at locations where no data is available for the past (Smerdon et al, 2011). Thus, even while these studies did not use predictors from Ireland, validation measures in these studies do indeed indicate skill for our area of interest (Luterbacher et al, 2004;Xoplaki et al, 2005;Pauling et al, 2006). Recently, it has been shown that even without explicitly including teleconnection patterns, reconstructions can still be skilful outside the area with good data coverage in the past (Werner et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…4.1 is an in-depth analysis of pre-famine vulnerability; in Sect. 4.2, using temperature and precipitation reconstructions from Luterbacher et al (2004Luterbacher et al ( , 2007, Xoplaki et al (2005) and Pauling et al (2006), we describe climate conditions in Ireland between 1739 and 1741; Sect. 4.3 looks at the impacts on, and coping strategies of, Irish society; finally, Sect.…”
Section: S Engler Et Al: the Irish Famine Of 1740-1741: Famine Vulnmentioning
confidence: 99%
See 2 more Smart Citations